2020
DOI: 10.1249/jsr.0000000000000787
|View full text |Cite
|
Sign up to set email alerts
|

Gamer's Health Guide: Optimizing Performance, Recognizing Hazards, and Promoting Wellness in Esports

Abstract: Electronic sports (esports), or competitive video gaming, is a rapidly growing industry and phenomenon. While around 90% of American children play video games recreationally, the average professional esports athlete spends 5.5 to 10 h gaming daily. These times and efforts parallel those of traditional sports activities where individuals can participate at the casual to the professional level with the respective time commitments. Given the rapid growth in esports, greater emphasis has been placed on identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 43 publications
1
43
0
1
Order By: Relevance
“…The potential hazards faced by esports athletes are similar to the hazards found in many sports, recreational and work environments, including musculoskeletal, ergonomic, biological and psychosocial hazards. The esports athlete's posture in a gaming chair, prolonged screen exposure and hundreds of repetitive movements during gaming sessions are contributing factors to the development of these hazards, to this we add that the average professional esports athlete spends 5,5 to 10 hours gaming daily (Emara et al, 2020), a considerable amount of daily life. Although esports are not a moderate to vigorous intensity activity, there are factors related to the level of physical activity and body composition that can condition the quality of training and decrease the risk of injuries especially spine and musculoskeletal pain, another aspect to consider is that esports are considered sedentary in nature due to the lack of body movement, but they can impose significant demands on the body due to rapid and continuous finger movements and concentration demands promoting physical and psychological stress (Hamari & Sjöblom), in addition it is common to find a high level of back pain and injuries due to the large amount of time players spend in repetitive positions.…”
Section: Introductionmentioning
confidence: 99%
“…The potential hazards faced by esports athletes are similar to the hazards found in many sports, recreational and work environments, including musculoskeletal, ergonomic, biological and psychosocial hazards. The esports athlete's posture in a gaming chair, prolonged screen exposure and hundreds of repetitive movements during gaming sessions are contributing factors to the development of these hazards, to this we add that the average professional esports athlete spends 5,5 to 10 hours gaming daily (Emara et al, 2020), a considerable amount of daily life. Although esports are not a moderate to vigorous intensity activity, there are factors related to the level of physical activity and body composition that can condition the quality of training and decrease the risk of injuries especially spine and musculoskeletal pain, another aspect to consider is that esports are considered sedentary in nature due to the lack of body movement, but they can impose significant demands on the body due to rapid and continuous finger movements and concentration demands promoting physical and psychological stress (Hamari & Sjöblom), in addition it is common to find a high level of back pain and injuries due to the large amount of time players spend in repetitive positions.…”
Section: Introductionmentioning
confidence: 99%
“…The present ndings revealed that most professional eSport athletes would induce physical fatigues and dry eyes after half-day (4-hour) and fullday (8-hour) training. Furthermore, similar to previous demographic studies, eSport athletes are required to sit with the same position for 5.5 to 10 h/day [3,5] or up to 14 h/day [2], leading to a sedentary lifestyle with an increased chance of fatigue and chronic injury as well as increased all-cause mortality [8,18]. The physical fatigue may be due to poor workplace practices (prolong posture, repetitive movement), competition stress, and burnout; while eye fatigues could also be related to prolonged visual attention to the screen and poor lighting environment [3].…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the esports ecosystem can be used to easily reach an exponentially growing viewership that already surpassed the viewership of most traditional sports (Kane and Spradley, 2017 ). The digital nature of esports allows more interaction and engagement of the fans than most traditional sports.…”
Section: Opportunities In Esportsmentioning
confidence: 99%
“…Like traditional athletes, esports players can also suffer career-ending injuries (Emara et al, 2020 ). According to DiFrancisco-Donoghue et al ( 2019 ), esports players are susceptible to chronic overuse injuries as gaming on a competitive level requires players to play for many hours a day.…”
Section: Opportunities In Esportsmentioning
confidence: 99%